(untitled) (Research, Society and Development, 2022)
Introduction: the metabolic syndrome (MS) is a set of risk factors, which together contribute to an increased risk of developing cardiovascular diseases, type 2 diabetes mellitus (DM2), various types of cancer, in addition to a greater chance of death. premature. Associated factors include increased visceral fat, low levels of high-density lipoprotein (HDL), high blood pressure, hypertriglyceridemia, and high fasting blood glucose. Objective: to describe the role of physical exercise in the treatment of patients with metabolic syndrome. Methodology: to prepare the research question of the review, the PICO strategy was used. Thus, the delimited research question was “Is physical exercise efficient in the treatment of metabolic syndrome?”. In it, we have P= Patients with metabolic syndrome, I= Physical exercises and O= Treatment of metabolic syndrome. From the establishment of the research keywords, the descriptors “Metabolic Syndrome”, Treatment, “Physical Exercises”, “Metabolic Syndrome”, Treatment and “Physical activity” were crossed; in the following databases: Virtual Health Library (VHL); National Library of Medicine (PubMed MEDLINE), Web of Science, Scopus, Scientific Electronic Library Online (SCIELO) and EbscoHost. Results and Discussion: Several studies have illustrated the significant improvement in clinical, anthropometric and biochemical parameters in the metabolic syndrome, as well as how exercise produces improvements in body composition, metabolism and cardiovascular system. Thus, this study was justified by the relevance of informing the population about the benefits that physical exercises can bring in the treatment of the syndrome. Final considerations: this study was justified by the relevance of informing the population about the benefits that physical exercises can bring in the treatment of the syndrome. Thus, it is an adequate and accessible intervention for health promotion among patients with this abnormality.